Shifts in the Humanitarian Space? Examining NGO–Military Engagements During the 2017 Crisis in Marawi, Philippines - Hall, Rosalie Arcala (Archīum Ateneo, 2021)
The increase in military deployments for operations other than war, and their co-location with humanitarian actors prompt an examination of how operational engagements are blurring boundaries between the two. Military-initiated coordination structures that bridge civilian and military spheres of activities are seen as signs of the securitization of the humanitarian space. Examining the dynamics between deployed Philippine military units and local non-governmental organizations (NGOs) in the humanitarian response to the 2017 Marawi siege, the former physically separated and subsumed humanitarian actions to kinetic goals. Using data from 48 interviews of commanders, NGO representatives and local government officials in 2018-2019, military-NGO interface was limited by military restrictions on mobility and by having a separate coordination platform benefiting soldiers and evacuees, respectively. Humanitarian NGOs are more willing to work with and are differential to the securitized space compared to human rights-based NGOs.